Sonata para violino e piano nº 3 de Liduino Pitombeira: uma visão retórica - Samuel Alessandro Granjense de Lima Saraiva (2003)
This work begins by forming an idea in the readers mind of what is a rhetorical speech; later it disposes and puts the parts of the rhetoric into a systematic arrangement and relates them with music. It has one chapter entirely dedicated to the life and works of composer Liduino Pitombeira. Following it, there is a formal and rhetorical analysis of the three movements of the above-mentioned composers Sonata for Violin and Piano No.3. Then, it shows the compilation of a series of conversations with the composer through the Internet about some points detected in the analysis. The work finishes with a conclusion that includes a final impression of the author on his contact with the rhetoric and onhaving intimately made its connections with music.